2016
DOI: 10.1016/j.ecoleng.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of design and operational parameters on ammonium removal by single-stage French vertical flow filters treating raw domestic wastewater

Abstract: 15Four pilot-scale single-stage vertical flow filters (of 2.25m² each), treating raw domestic 16 sewage, were studied over 20 months in order to assess the impact of different designs 17 and operational conditions on treatment efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 23 publications
2
13
0
3
Order By: Relevance
“…The highest TN removal was observed in Darżlubie (91.7%). Achieved results are similar to data described previously in [14,6,15,16]. During measurement period facilities worked with various effectiveness of nitrogen removal.…”
Section: Hf + Vf Configurationsupporting
confidence: 84%
“…The highest TN removal was observed in Darżlubie (91.7%). Achieved results are similar to data described previously in [14,6,15,16]. During measurement period facilities worked with various effectiveness of nitrogen removal.…”
Section: Hf + Vf Configurationsupporting
confidence: 84%
“…Several studies have focused on nitrogen (N) removal using different media (e.g., Millot et al, 2016;Wu et al, 2015;Zhang et al, 2012;Zurita et al, 2009). Zhang et al (2015) reviewed the performance of CWs in tropical and sub-tropical regions and concluded that the media significantly affected the removal efficiencies of TN,and NO 3 -N in vertical flow constructed wetland (VFCW) systems.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the effluent from the WWTP always respected the water quality target set in the design phase ( Figure 2). The t-tests confirm that outlet concentrations are significantly lower than influent concentrations for both OUT 1 and OUT 2, with a significance lower than 0.05 for COD, BOD 5 , TN, N-NH 4 + , and TSS, and lower than 0.1 for TP (see Table S1 in Supplementary online material).…”
Section: Water Quality Dataset Analysismentioning
confidence: 82%
“…Indeed, the solid materials from wastewater will create an organic top layer on the surface area and has to be removed after 10-15 years, i.e., when it is already stabilized and can be used as soil conditioner [4]. FRBs are very efficient in the removal of suspended, dissolved organic matter, and pathogens and have a high nitrification capability, with a relevant contribution due to the first stage [5]. Higher denitrification and total nitrogen removals are achievable with the adoption of a saturation bottom layer [6].…”
Section: Introductionmentioning
confidence: 99%